A Randomized Clinical Trial of Gokshuradi Ghan Vati and Gokshuradi Rasayana Churna Along with Swarjikadya Taila Karna Pichu in the Management of Karnasrava with Special Reference to Chronic Suppurative Otitis Media (AYUSHDHARA, 2023)
Karnasrava means flow, oozing, dropping, exudate or discharge through ear. Karnasrava correlates in modern science with C.S.O.M. C.S.O.M. are a chronic inflammation of the middle ear which is the result of an initial episode of acute otitis media and characterized by recurrent discharge from the middle ear through a tympanic perforation. According to WHO prevalence of c.s.o.m. involves 65-330 million individuals with draining ears, 60% of whom (39-200 million) suffers from significant hearing impairment. Material and Method: The present study is done with 30 patients of Karnasrava divided into two groups, 15 patients were treated with Gokshuradi Ghan Vati along with Swarjikadya Taila Karna Pichu rest 15 were treated with Gokshuradi Rasayana Churna along with Swarjikadya Taila Karna Pichu. Result: It showed that Gokshuradi Ghana vati along with Swarjikadya Taila Karna Pichu showed slightly significant as compared to Gokshuradi Rasayana Churna along with Swarjikadya Taila Karna Pichu. Discussion: Swarjikadya Taila is acts as Sthanika Snehana and Swedana, thus causes increased local warming, pseudo-inflammation and increased blood circulation there by helping in better absorption to affected site. Most of the drugs of Gokshuradi Ghana Vati have Rasayana, Kasa-Shwashara, Vedanasthapana, Shulaprashmana, Shothahara, Balya, Vranashodhana, Vranaropana, Krimighna, Deepana, Pachana properties. Conclusion: Both groups showed good result in the management of Karnasrava but Gokshuradi Ghan vati along with Swarjikadya taila Karna pichu showed slightly significant as compared to Gokshuradi Rasayana Churna along with Swarjikadya Taila Karna Pichu.